The Dynamics of ICT and Economic Growth in Morocco: A Quantitative Approach - Mohamed, Echaoui; Karim, Mohamed; Omayma, Mouti; Ahmed, Touzani (International Journal of Economics and Financial Issues, 2026)
This research empirically examines the effect of Information and Communication Technologies (ICT) on Morocco’s economic growth over the period 1998–2022. It is based on an extended Solow growth model that incorporates ICT as a production factor complementing capital and labor. A composite ICT index is constructed using data from the International Telecommunication Union (ITU), encompassing dimensions of access, usage, and skills. The econometric approach adopted is the AutoRegressive Distributed Lag (ARDL) model, which captures both short- and long-term dynamics. The results reveal a cointegration relationship between ICT and economic growth, validated by the Bounds testing approach of Pesaran et al. (2001). In the short run, ICT has a positive and significant impact on growth, while inflation and the labor force have a negative effect. In the long run, ICT, foreign direct investment (FDI), labor force, and gross fixed capital formation contribute positively to economic growth. The study confirms the pivotal role of ICT as a driver of economic transformation and emphasizes the importance of sustained investment in technology and education. It recommends strengthening digital infrastructure, improving workforce skills, and attracting more foreign investment to foster inclusive and sustainable growth.